ASME 2019 13th International Conference on Energy Sustainability 2019
DOI: 10.1115/es2019-3807
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Metal Electrodes on the Charge Extraction of Inverted Perovskite Solar Cells

Abstract: A perovskite solar cell in the inverted configuration was modeled and simulated to investigate the impact of the cathode work function on the cell performance. The model utilized the drift-diffusion current equations, coupled with Poisson’s equation and continuity equations to determine the J-V characteristics, the band diagram, and the external quantum efficiencies. It was found the power conversion efficiency (PCE) tended to decrease with the increasing work functions of the metal cathode. The device using l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The authors concluded that employing metals with high work functions, such as Au, caused a misalignment of energy levels within the light-absorbing layer towards the cathode, creating an upward band bend that hindered effective electron transport and consequently reduced solar cell efficiency. Similarly, Gong et al 85 conducted simulation work using MAPI perovskite to investigate the impact of metal cathodes on iPSCs, and they also concluded that metals like Au and Pt could generate an energy barrier towards the cathode. Fig.…”
Section: Inuence Of Masi/cui Thickness and The Different Back Contac...mentioning
confidence: 99%
“…The authors concluded that employing metals with high work functions, such as Au, caused a misalignment of energy levels within the light-absorbing layer towards the cathode, creating an upward band bend that hindered effective electron transport and consequently reduced solar cell efficiency. Similarly, Gong et al 85 conducted simulation work using MAPI perovskite to investigate the impact of metal cathodes on iPSCs, and they also concluded that metals like Au and Pt could generate an energy barrier towards the cathode. Fig.…”
Section: Inuence Of Masi/cui Thickness and The Different Back Contac...mentioning
confidence: 99%